Eksistensi Agama Shinto dalam Pelaksanaan Matsuri di Jepang - Adriani, Sri Dewi (Bina Nusantara University, 2007)
Japan is one of the nations having an extensive historical culture, as well as the system of faith or religion. The existence of religion, as a part of their life, has been streaming from the ancient time (pre-modern) up to present. The implementation of their religious life is very unique and fascinating. Other remarkable issues is about the tight relationship among the religions especially Shinto with the festival performances which is held in Japan along the seasons.